Davidson$1 (Bs Principles and Practice of Medicine/s - Ralston, S.H; Penman, I.D.; Strachan, M.WJ; Hobson, R.p. (London Elsevier, 2018)
Since it was first published this comprehensive text has met the requirements of several generations of medical students preparing for their examinations, while serving as a valuable reference for doctors in training. Includes a revised chapter Principles of Medical Psychiatry concentrating on the important aspects of major psychiatric illness as it relates to medical practice and a new chapter on the Principles of Critical Care Medicine brings together the major conditions that are handled in the ITU.
osc 24/10/2022
Keywords: Internal medicine; Medicine; Pathology